P247 Quality of life and sexual function amongst women with persistent genital discharge or dermatoses. (18th May 2015) - Vora, Nina; Whitlock, Gary; Brima, Nataliya; Robinson, Angela
Abstract : Background: Existing data on the effect of genital discharge and dermatoses on the quality of life (QoL) and sexual function (SF) in women with genital complaints are limited. Objectives: To study the impact of our specialist clinic for recurrent genital problems on QoL and SF using two validated questionnaires: dermatology life quality index (DLQI) and female sexual function index (FSFI). Methods: All women attending this specialist clinic during 2013 were invited to complete both DLQI and FSFI. Questionnaires were resent six months later or completed at follow-up attendance. Paired questionnaires were analysed using Wilcoxon-signed-rank tests. Results: We received 143 responses: 99 dermatological complaints and 44 discharge complaints. Both complaints have a detrimental effect on QoL (mean ± SD quality of life scores 8·4 ± 6·6, moderate effect on QoL vs published general population score between 0 and 1 in validation studies). SF was also impaired (score 19.6 ± 6.9, vs published general population mean score 30.5 ± 5.29). 13 patients fully completed DLQI pre and post clinic intervention; there was significant improvement in DLQI scores (median pre-intervention vs post-intervention scores, interquartile range (IQR): 15 (12–18) vs 8 (6–12), P = 0.013). FSFI scores did not significantly improve (18.55 (16.5–22.5) vs 18.5 (14.0–22.7), P = 1.000). Discussion/conclusion: Both QoL and SF are impaired in many women presenting with recurrent genital complaints. Appropriate assessment and management by senior physicians can significantly improve QoL in these women supporting the role of specialist clinics. There remains significant impairment to SF, warranting research into affordable interventions.